Managing groundwater for building resilience for sustainable agriculture in South Asia - Sikka, Alok; Alam, Mohammad Faiz; Pavelic, Paul (Wiley, 2021)
South Asia's heavy reliance on groundwater for irrigated agricultural production supports the livelihoods of tens of millions of smallholder farmers but is being undermined by rampant overexploitation of groundwater. Without major intervention, this is expected to be further exacerbated by growing demand and climate change. Groundwater management, scientific and evidence-based, can make an important contribution to managing unsustainable groundwater use and strengthening the climate resilience of farmers due to groundwater's unique storage characteristics. This study brings together a set of strategies and solutions to better manage groundwater that cover the augmentation of groundwater recharge through managed aquifer recharge, management of groundwater demand through participatory groundwater management and other methods, and the harnessing synergies of co-dependent sectors. The opportunities, constraints and available evidence for each are analysed and the boundaries, barriers and specificities identified to establish entry points for positive change through policies and implementation programmes.